ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE JUST IN TIME UNTUK MEMINIMUMKAN BIAYA PERSEDIAAN (STUDI KASUS PADA UD. RAYA KOTA KEDIRI) - Quinn Nakula Junior; Taufik Akbar; Karari Budi Prasasti (Cahaya Ilmu Bangsa, 2024)
Abstrack This research aims to determine the cost of raw material inventory, both using conventional and conventional methods Just In Time (JIT), at UD. Raya Kediri City. The type of research used is quantitative descriptive aimed at solving certain problems and achieving a deeper understanding of an event. The type of data used includes primary data from interview techniques and secondary data obtained from raw material inventory data. The analysis used in this research is analysis Just In Time (JIT). The place of this research is the UD Cracker Factory. Raya Kediri City. The raw material studied was wheat flour. The results of the raw material inventory research were calculated using Just In Time (JIT) obtained 21,600 kg with an ordering frequency of 4 times a month, and the total cost of raw material inventory using the Just In Time (JIT) is IDR. 153,140,000,-.